Sosialisasi permainan hockey indoor dan memasyarakatkan hockey - Abdul Rahman; Syahruddin Syahruddin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Indoor hockey was developed in Germany during the 1950s, quickly spreading to other European countries. FIH (International Hockey Federation) recognized indoor hockey in its constitution in 1968. The room hockey rules were issued by the International Hockey Federation (FIH) on January 1, 2017. This regulation contains the playing field, the composition of players, team captains, player clothing and player equipment, matches and results of matches, starting and restarting matches, ball out of the field, scoring method, player behavior, special goalkeeper and goalkeeper, game judge (referee), punishment, penalty taking procedure, personal punishment, and arbitration. The results of the community service activities found that all community service participants felt enthusiastic and there was a desire to play hockey, especially indoor hockey games, on the grounds that indoor hockey games were played indoors.